3D reticulated carbon nitride materials high-uniformly capture 0D black phosphorus as 3D/0D composites for stable and efficient photocatalytic hydrogen evolution. Issue 2 (11th December 2018) - Song, Ting; Zeng, Gongchang; Zhang, Piyong; Wang, Tingting; Ali, Atif; Huang, Shaobin; Zeng, Heping
Abstract : A facile strategy to fabricate a uniform 3D/0D hybrid as a stable and excellent photocatalyst utilizing the self-capturing property of CN-4N. Abstract : Black phosphorus has recently emerged as an excellent 2D semiconductor with high charge-carrier mobility and wide tunable bandgap for photocatalysis. In this research, a simple method was developed to manufacture reticulated carbon nitride materials (CN-4N). Utilizing the self-capturing property of CN-4N to capture black phosphorus quantum dots (BQ) uniformly dispersed in aqueous solution, BQ were successfully implanted in the interior surface of CN-4N to form a unique structure instead of the normal exterior surface contact pattern. The optimized CN-4N(BQ) showed good stability and achieved an excellent hydrogen production rate of 13.83 mmol h −1 g −1, which was 3.3- and 35.5-fold higher than that of CN-4N and bulk CN (NCN), respectively. The experimental results illustrated that the greatly improved photocatalytic performance of CN-4N(BQ) was attributed to the joint actions of the abundant active sites provided by the ultra-porous structure, the excellent vis-NIR absorption capability, the spatially separated reactive sites for the redox reaction, and the greatly enhanced photoinduced electron–hole separation efficiency. This research provides novel insight for the rational fabrication of CN-based hybrids for various applications.